Analysis of Risk Factors for Stunting in Central Java - Sri Sumarni; Suryati Kumorowulan; Suharyo Hadisaputro; Eka Apriadi Farkhati Nafi’ah (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
The prevalence of stunting in Indonesia was 24.4% in 2021 in Central Java at 20.9%, which is still above the WHO target of 20%. There are many direct and indirect risk factors that cause stunting events. The purpose of this study is to analyze the risk factors for stunting events in Central Java. This research is an observational study with a cross-sectional approach. The collected data was analyzed using the Chi-Square test to assess the relationship between the independent variable (risk factors) and the dependent variable (stunting incidence). In addition, the odds ratio calculation is used to determine the risk level of each factor in influencing the incidence of stunting. The population is all mothers who have toddlers aged 0-59 months in Central Java Province. Data were collected via Google Form for two weeks in December 2023 using the Accidental Sampling technique with a total of 2671 mothers involved in this research. The result shows that the prevalence of stunting is 24.3%. There was no relationship between maternal parity OR 0.865, working mother OR 0.878, maternal BMI OR 0.898, economic status OR 0.954, and the incidence of stunting in toddlers. There was a relationship between maternal education OR 2.120, maternal height OR 1.955, exclusive breastfeeding OR 1.616, the diet OR 3.160, gestational age OR 1.410, the birth weight OR 1.670, and the incidence of stunting in toddlers. It is concluded that several factors collaborate to the high number of stunting, which are maternal education, maternal height, exclusive breastfeeding, diet, gestational age, and birth weight. Further research needs to consider a wider sample, the number of other risk factors which are competency of health provider to diagnose stunting, family support, and extend the length of observation time.